(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Two Aspergillus spp. namely A. funiculosus (Za) and A tamarii (Zc) were isolated, purified, identified and studied for their protease activity under some selected environmental condition and nutritional factors. The strains showed the maximal activity of protease after 5 days (Za) and 6 days (Zc) of incubation at 27ºC in a medium containing peptone as nitrogen source with pH 5.0. Isolate Za showed highest protease activity in the presence of fructose as carbon source, at 35 °C, with pH 6.0 and 2.5% casien as substrate concentration. Where as for Zc it was starch as carbon source, temperature 40 °C, with pH 7.0 and 2% casien ,the isolate showed highest enzyme activity. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13390 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):91-98, 2009